Arbitrary-order economic production quantity model with and without deterioration: generalized point of view - Rahaman, Mostafijur; Mondal, Sankar Prasad; Shaikh, Ali Akbar; Ahmadian, Ali; Senu, Norazak; Salahshour, Soheil (SpringerOpen, 2020)
The key objective of this paper is to study and discuss the application of fractional calculus on an arbitrary-order inventory control problem. Using the concepts of fractional calculus followed by fractional derivative, we construct different possible models like generalized fractional-order economic production quantity (EPQ) model with the uniform demand and production rate and generalized fractional-order EPQ model with the uniform demand and production rate and deterioration. Also, we show that the classical EPQ model is the particular case of the corresponding generalized fractional EPQ model. This greatly facilitates the researcher a novel tactic to analyse the solution of the EPQ model in the presence of fractional index. Furthermore, this attempt also provides the solution obtained through the optimization techniques after using the real distinct poles rational approximation of the generalized Mittag-Leffler function.